Fiscal Decentralization, Economic Growth and Regional Development Inequality in Eastern Indonesia - Nur Farida; Agus Suman; Rachmad Kresna Sakti (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
This study analyzes the relations between fiscal decentralization, economic growth, and regional development inequality in Eastern Indonesia using 2016-2019 panel data of thirteen Eastern Indonesia provinces obtained from Statistics Indonesia and the Directorate General for Fiscal Balance. Using simultaneous equations estimated through the Three-Stage Least Squares, this study finds that fiscal decentralization has not fully supported economic growth and correct the inequality in eastern Indonesia’s regional development. The mandate for managing the budget has not been optimally used by the local governments, indicated by poor allocation for productive expenditures and its decreasing proportion during the research period. It is caused by poor human resource quality in budget planning and management, which finally hinders the quality of public service and economic growth. Supports from physical and human capital are required to keep up with the occurring economic activities so that inequality in regional development in the area can be reduced.